ORGANIC GEOCHEMICAL STUDY OF LAKE SEDIMENTS AND ALGAL MATS FROM THE LUTZOW-HOLM BAY REGION, ANTARCTICA - マツモト, ゲンキ; オオタニ, シュウジ; ムラヤマ, ハルタ; ワタヌキ, クニヒコ; トリイ, テツヤ; MATSUMOTO, Genki I.; OHTANI, Shuji; MURAYAMA, Haruta; WATANUKI, Kunihiko; TORII, Tetsuya (National Institute of Polar Research, 1993)
P(論文) The organic geochemical study of hydrocarbons and fatty acids in lake sediments and algal mats from the Lutzow-Holm Bay region, East Antarctica was carried out to elucidate their features for the paucity of vascular plants in relation to source organisms. Normal alkanes ranging in carbon chain length from C_<15> to C_<35> with a predominance of odd-carbon numbers were found in the sediment and algal mat samples, together with monomethyl-and dimethyl-branched alkanes and/or alkenes. Interestingly, long-chain n-alkenes were present in some sediment samples. Also, triterpenes, such as hop-22(29)-ene and 17β(H), 21β(H)-hopane, and 5α(H), 14α(H), 17α(H)-C_<27>-C_<29> steranes were found in most samples. Normal alkanoic acids in carbon chain length ranging from C_<10>-C_<32> with a predominance of even-carbon numbers were detected in the samples, along with iso-and anteiso-alkanoic acids (C_<12>-C_<17>) and n-alkenoic acids (C_<16> and C_<18>). Unusually, long-chain n-alkanes and n-alkanoic acids (>C_<19>) were major components in certain samples. The major organisms in algal mats were Cyanophyceae (Nostoc sp. or Phormidium sp.), Bacillariophyceae (Amphora veneta, Coscinodiscus sp., Fradilariopsis curta or Navicula cryptocephala) or Chlorophyceae (Cosmarium clepsydra or Oedogonium sp. These algae and cyanobacteria are commonly distributed in Antarctic lakes and ponds. However, the major organisms in the sediments are all Bacillariophyceae, suggesting that settled organic matter in the sediments is degraded largely after sedimentation, and only Bacillariophyceae remained. Also, n-alkenoic acid/n-alkanoic acid ratios probably reflect the degree of destruction of organic matter. The abundance of alkenes may be explained by low environmental temperatures in the region, since it is known that unsaturated compounds in some plankton increase with decreasing ambient temperatures. The absence of thermally matured triterpanes and steranes indicates ...